Normal Values and Reproducibilitiy of Electric Current Perception Threshold in Sensory Fibers - Reza Salman-Roghani; Afshin Adib (University of Social Welfare and Rehabilitation Sciences, 2006)
Objective: Routine electrodiagnosis (EMG-NCS) has some shortcomings in the evaluation of peripheral nervous system, auch as autonomous nervous system evaluation, in pure sensory radiculopathies and acute hyperesthetic stages of neuropathies. Quantitative sensory testings such as current perception threshold (CPT) with electrical stimulations are suggested for above mentioned pathologies. Ttest results should be compared with a normal value of similar identical population. This study is conducted to determine normal value and reproducibility of CPT in the Iranian population. Materials & Methods: Fifty normal volunteers (32 men, 18 woman) in the range of 20-40 years without exclusion criteria (such as neuro- musculoskeletal disorders, diabetes mellitus and alcoholism) were recruited with simple randomized selection and CPT test was conducted on C8 (4th finger) and L5 (1st Toe)dermatomes. To determine test's reproducibility, 6 persons (4 men, 2 women) were examined 3 times a day, 2 day per week. Collected data were analyzed to determine mean and standard deviation. Results: Normal values of CPT test was defined as one standard deviation from mean of our CPT data. These values are in C8 dermatome 2000 Hz: 2.04± 47 250 Hz: 0.75±0.25 5 Hz: 0.76±0.3 and for L5 dermatome 2000Hz: 2.83± 0.73 250 Hz: 1.24 ± 45 5Hz: 0.76± 0.3 To determine our results reproducibility and reliability, Alpha- cronbach (existed in SPSS software) was used and %98.5 & 99% were obtained for C8 & L5 dermatomes respectively. Conclusion: Our findings are about C8 & L5 dermatomes which could be used as a normal Values for such dermatomes. Regarding to its good correlation with international results we can use international references as a normal Valueswith consideration of each clinic's reproducibility should be assessed individually.